CRACK-FILL PORPHYROBLASTESIS - Barker A.J. (My University, 2002)
Garnet-mica schists from the Scottish Highlands provide new insight into an important mechanism of phyllosilicate growth, termed 'crack-fill porphyroblastesis'. It is shown that grain boundary dilatancy, microcracking and porphyroblast-matrix decoupling all play a significant role in facilitating growth in regimes of noncoaxial shear. With respect to chlorite porphyroblasts, there are three growth stages. Following nucleation, the initial phase of growth is by progressive matrix replacement, to preserve inclusion trails of fine carbonaceous material. The second growth stage produced new optically continuous inclusion-free chlorite on the {001} margins of those crystals at a high angle to the schistosity. This growth results from decoupling at the porphyroblast-matrix contact on those margins at a high angle to the principal axis of extension. The development of dilatant cracks at porphyroblast margins provides a sink for material migrating down P f and chemical potential gradients. This causes precipitation of new optically continuous 'clear' chlorite on the pre-existing, heavily included core. The porphyroblast-matrix boundary continues to dilate after porphyroblast growth had terminated, producing plano-convex quartz-rich strain shadows. Similar growth behaviour is recognised in biotite porphyroblasts, indicating that 'crack-fill porphyroblastesis' is an important growth mechanism for phyllosilicates in actively deforming metamorphic rocks. It also indicates that decoupling and crack-fill development at porphyroblast margins could be important in controlling the pattern of material transfer, and may have significant implications for matrix permeability and fluid-flow characteristics.
Keywords: FLUID FLOW; INCLUSION TRAILS; MICROCRACKS; PORPHYROBLAST GROWTH